Tarra & Bella : the elephant and dog who became best friends - Buckley, Carol, 1954- (New York : G.P. Putnam's Sons, 2009)
Recounts the true story of Tarra, an elephant who befriended a stray dog named Bella at the Elephant Sanctuary in Tennessee.
Publisher's Weekly
3.1
K-3
K-3
Keywords: Asiatic elephant -- United States -- Juvenile literature; Dogs -- United States -- Juvenile literature; Social behavior in animals -- Juvenile literature; Animal behavior; Asiatic elephant; Dogs; Elephants; Asiatic elephants; Dogs -- United States; Elephants -- United States; Social behavior in animals; Elephant Sanctuary (Tenn.) -- Juvenile literature; Elephant Sanctuary (Tenn.); Elephant Sanctuary (Tenn.); Picture books for children